PENGENALAN TEKNOLOGI KOMPUTER DAN PEMANFAATAN MEDIA SOSIAL DI ERA 4.0 DI SMK BUDI MURNI 3 - Hansen Louisther; Edison Hatoguan Manurung; Ghurabillah Ghurabillah; Retno Indriyati Kusuma; Mangaraja L Saragi (Indonesian Collaboration Journal of Community Services, 2022)
One of the implementations in higher education is education and teaching.the author in this case we students of informatics engineering and industrial engineering have carried out real work lecture activities in one of the school institutions, namely at smk budi murni 3 which is addressed at jl. Sawah besar – duren sawit east jakarta with some teaching to students or students of class xii with the theme introduction of computer technogi and social media utilization in era 4.0. On this occasion, we as students of mpu tantular university, namely the informatics engineering and industrial technology study program, aim to conduct this learner with the aim that in the next generation understand and understand it will be very important to understand the development of technology, especially in the field of computers and their use